Evidence for a Role of Connexin 43 in Trigeminal Pain Using RNA Interference In Vivo - Ohara, Peter T. (American Physiological Society, 2008)
The importance of glial cells in the generation and maintenance of neuropathic pain is becoming widely accepted. We examined the role of glial-specific gap junctions in nociception in the rat trigeminal ganglion in nerve-injured and -uninjured states. The connexin 43 (Cx43) gap-junction subunit was found to be confined to the satellite glial cells (SGCs) that tightly envelop primary sensory neurons in the trigeminal ganglion and we therefore used Cx43 RNA interference (RNAi) to alter gap-junction function in SGCs. Using behavioral evaluation, together with immunocytochemical and Western blot monitoring, we show that Cx43 increased in the trigeminal ganglion in rats with a chronic constriction injury (CCI) of the infraorbital nerve. Reducing Cx43 expression using RNAi in CCI rats reduced painlike behavior, whereas in non-CCI rats, reducing Cx43 expression increased painlike behavior. The degree of painlike behavior in CCI rats and intact, Cx43-silenced rats was similar. Our results support previous suggestions that increases in glial gap junctions after nerve injury increases nociceptive behavior but paradoxically the reduction of gap junctions in normal ganglia also increases nociceptive behavior, possibly a reflection of the multiple functions performed by glia.